URGENSI UNDANG-UNDANG TENTANG LEMBAGA KEPRESIDENAN DALAM SISTEM PEMERINTAHAN REPUBLIK INDONESIA DIKAITKAN DENGAN EKSISTENSI UNDANG-UNDANG LEMBAGA-LEMBAGA NEGARA LAINNYA - Muhammad Jodi Wiranto; Ahmad Redi (Jurnal Hukum Adigama, 2021)
“The President is referred to as the Head of State as well as the Head of Government and is the central figure of the Presidential institution in implementing decision-making in the Indonesian government system. According to Article 1 paragraph (1) of the 1945 Constitution of the Republic of Indonesia, hereinafter referred to as the 1945 Constitution of the Republic of Indonesia. The State of Indonesia is a unitary state in the form of a Republic. A Republic is a country headed by a president . Almost all state institutions have laws, while the government of the president and vice president do not have laws. Even though it is very important what needs to be regulated in the Duties and Authorities of the Vice President , the relationship between the President's institution and other high state institutions, regarding the rights, obligations and prohibitions of the presidential institution. The type of research in this legal research is descriptive normative or doctrinal legal research which is carried out through a critical, logical and systematic identification process using a historical conceptual approach and a judicial analysis approach (legal analysis), namely an approach to see the historical conception of the Presidential institution according to the period of time. the power of the Presidential in the Constitution as well as the norms governing the Presidential institution in the Act and their urgency and are associated with the existence of laws on other state .